FIBER CLASSIFICATION, PHYSICAL AND OPTICAL PROPERTIES OF RECYCLED PAPER - (:unkn) unknown (EDITURA ACAD ROMANE, 2021)
In this study, reference papers prepared in accordance with the INGEDE 11p standard (International Association of the Deinking Industry) were recycled three times. Initially, reference papers were subjected to wetting, pulping, storage, deinking, dispersing and bleaching processes. At the end of these processes, test papers were produced and their optical characteristics were examined. The brightness value of writing papers (of 80 grams) was determined to be of 86%, following the TS 11610:2017 standard. In order to bring the brightness of the produced laboratory test papers to the specified value, double-stage bleaching was applied: with 0.4% FAS in the first stage and H2O2 in the second stage. The physical and optical properties of the test papers that reached the standard brightness value were determined. Overall, the final products were recycled three times. At the end of the third recycling stage, changes in paper fibers were examined. As a result, it was observed that the breaking, tear and burst resistance of the obtained papers gradually decreased at the end of each recycling stage. In addition, because of the narrowing fiber surface, it was determined that the opacity value of the paper decreased at the end of each recycling stage. According to the fiber classification results, the fiber size shrank at the end of the third recycling stage and a large part of the fibers remained in the 200 mesh. Paper fibers are recycled 3.6 times in Europe. This rate is approximately 2.4 times higher than the world average. This study offers interesting results regarding cellulose recycling, which has gained great importance in recent years.
Keywords: INGEDE; recycling; optical properties; physical properties; fiber classification; WATER